Insights Into the Biodegradation of Lindane (γ-Hexachlorocyclohexane) Using a Microbial System - Zhang, Wenping; Lin, Ziqiu; Pang, Shimei; Bhatt, Pankaj; Chen, Shaohua (Frontiers in Microbiology, 2020)
Lindane (γ-hexachlorocyclohexane) is an organochlorine pesticide that has been widely used in agriculture over the last seven decades. The increasing residues of lindane in soil and water environments are toxic to humans and other organisms. Large-scale applications and residual toxicity in the environment require urgent lindane removal. Microbes, particularly Gram-negative bacteria, can transform lindane into nontoxic and environmentally safe metabolites. Aerobic and anaerobic microorganisms follow different metabolic pathways to degrade lindane. A variety of enzymes participate in lindane degradation pathways, including dehydrochlorinase (LinA), dehalogenase (LinB), dehydrogenase (LinC), and reductive dechlorinase (LinD). However, a limited number of reviews have been published regarding the biodegradation and bioremediation of lindane. This review summarizes the current knowledge regarding lindane-degrading microbes along with biodegradation mechanisms, metabolic pathways, and the microbial remediation of lindane-contaminated environments. The prospects of novel bioremediation technologies to provide insight between laboratory cultures and large-scale applications are also discussed. This review provides a theoretical foundation and practical basis to use lindane-degrading microorganisms for bioremediation.